Assessing the Role of TRIPS Agreement for Inaccessibility and Un-affordability of Essential Medicines in Nigeria - Dubagari, Umar Abubakar (Journal of Commerce and Trade, 2015)
Intellectual property rights (IPRs) protection was not recognised in Nigeria and essential medicines were accessible and affordable to all but reverse is the case with the implementation of TRIPS agreement on IPRs. This resulted in inordinate policy formulation and implementation that exacerbates the public health care despite Nigeria’s endowment with enormous human and natural resources. This paper argues that patents protection hinders access and affordability to essential medicines in Nigeria. It also argues that pharmaceutical companies prevent developing countries from utilising the TRIPS flexibilities to access essential medicines for their citizens. It concludes that access and affordability to essential medicines are additional challenges to Nigeria. The paper is based on the anti-corporate globalisation movement theory. The theory advocates for a world structured by human values other than greed and domination, one less dominated by the culture and values of global capital. The economic, political, and cultural interconnectedness signified by globalisation is irreversible and possibly a good thing, this interconnection, could potentially serve the interests of people and the earth, not just the elites. Although the rich and powerful have shaped globalisation in their interest, the anti-globalisation theory is a counter-movement that seeks to reshape the interconnected world in the interests of people and the planet.